Correlation between ovarian follicular development and Hippo pathway in polycystic ovary syndrome - Zichao Huang; Tianyue Xu; Chunling Liu; Honghui Wu; Linglin Weng; Jieyu Cai; Na Liang; Hongshan Ge (BMC, 2024)
Abstract Background For women of childbearing age, the biggest problem caused by polycystic ovary syndrome (PCOS) is infertility, which is mainly caused by anovulation, abnormal follicular development, proliferation of small antral follicles, and cystic follicles. The mechanism underlying its occurrence is not clear. The abnormal proliferation and development of follicles in PCOS patients is a complex process, which is affected by many factors. The objective of this study was to investigate the relationship between the Hippo pathway and follicular development in PCOS, and to further explore this relationship by using the YAP inhibitor verteporfin (VP). Method 30 3-week-old BALB/C female rats were randomly divided into control group (n = 10), DHEA group (n = 10) and DHEA + VP group (n = 10). The morphology of ovary and the degree of follicular development were observed by HE staining, and the expression and location of AMH in ovarian follicles were observed by immunofluorescence. The ovarian reserve function index AMH, cell proliferation index PCNA and the ratio of Hippo pathway related proteins MST, LATS, YAP, P-YAP and P-YAP/YAP were detected by Western blot. Results After dividing 30 3-week-old female mice into control, dehydroepiandrosterone (DHEA; model of PCOS), and DHEA + VP groups, we found that the number of small follicles increased in the DHEA group compared to the control group. Additionally, in the DHEA group compared to the control group, anti-müllerian hormone (AMH; ovarian reserve index) increased, proliferating cell nuclear antigen (PCNA; cell proliferation index) decreased, and upstream (MST and LATS) and downstream (YAP and p-YAP) proteins in the Hippo pathway increased, though the p-YAP/YAP ratio decreased. VP ameliorated the increases in AMH, MST, LATS, YAP and p-YAP, but did not ameliorate the decrease in the p-YAP/YAP ratio. Conclusions This study indicates that the increased small follicles in the ovaries and changes in ovarian reserve and cell proliferation may be closely related to Hippo pathway activation. This suggests that the Hippo pathway may be an important pathway affecting the proliferation and development of follicles and the occurrence of PCOS.